Evaluasi Penggunaan Obat Antihipertensi pada Resep Pasien BPJS RSUD Kota Mataram yang Ditebus di Apotek KF 134 Pejanggik dan KF 458 Catur Warga Berdasarkan ATC/DDD dan DU 90% - Hamzani, Yogi Mujizat; Andayani , Tri Murti; Dewi, Lucia Vita Inandha (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: Hypertension is a persistent condition of high blood pressure (systolic >140 mmHg or diastolic >90 mmHg). As a chronic disease requiring long-term treatment, the therapy for hypertensive patients needs to be evaluated regularly. Objective: This study aimed to determine the consumption profile of antihypertensive drugs using the ATC/DDD and DU 90% methods and to assess their compliance with the National Formulary (FORNAS). Methods: This research used a cross-sectional design with retrospective data collection. The samples were prescriptions for BPJS hypertension patients from Mataram City Hospital for the period of January-December 2024, redeemed at KF 134 Pejanggik Pharmacy and KF 458 Catur Warga Pharmacy. The data were analyzed using the Anatomical Therapeutic Chemical/Defined Daily Dose (ATC/DDD) and Drug Utilization 90% (DU 90%) methods. Results: The results showed that the most consumed antihypertensive class was ARBs, specifically candesartan, with a value of 13,082.25 DDD/1000 PPD at KF 134 Pejanggik and 7,215.33 DDD/1000 PPD at KF 458 Catur Warga. The drugs included in the DU 90% segment were candesartan, ramipril, amlodipine, and bisoprolol at both pharmacies, with the addition of valsartan at KF 134 Pejanggik. Compliance with drug use guidelines for FORNAS was 92% at KF 134 Pejanggik Pharmacy and 90% at KF 458 Catur Warga Pharmacy. Conclusion: The use of antihypertensive drugs in both pharmacies is in accordance with FORNAS, with high compliance percentages, indicating rational drug prescribing practices.